Penyelesaian Sidang Adat Kasus Kekerasan Dalam Rumah Tangga Pada Masyarakat Hindu Kaharingan (Perspektif Hukum Hindu) - Ni Ketut Ayu Marheni; Derson Derson; I Made Suyasa (Satya Dharma : Jurnal Ilmu Hukum, 2022)
This reaserch about harsness in Tumbang Mantuhe, Manuhing Raya District, Gunung Mas Regency which have been made by the people in Tumbang Mantuhe village who violate the law number 23 of 2004. This phenomenon occurred based on observations that had occurred in the households of the Hindu Kaharingan community in Tumbang Mantuhe Village which were resolved by Hindu customary law. Based on research, suspicion of wife, lack of communication, lack of affection, lack of harmony, economy, and infidelity are the factors of domestic violence. Meanwhile, violation of law, psychological violence, biological violence, and not providing for the wives. Then the settlement process, through deliberation and consensus which is completed by the customary mantir, witnesses, community leaders, religious leaders, and the families of the parties to the dispute by carrying out various processes, namely the existence of reports, mediation and customary hearings as well as customary sanctions.